Writings on the wall: religious syncretism through graffiti in Northeast Brazil (Escritos nos muros: sincretismo religioso através dos grafitos no Nordeste do Brasil) - Dann, Graham Michael Stuart (Ciência & Trópico, 2011)
RESUMO O sincretismo entre o catolicismo e os cultos Afro-brasileiros é um fenômeno his¬tórico bem documentado. Este estudo inicial busca enfatizar o grau de interpenetração religiosa e contemporânea analisando o conteúdo dos grafitos que enfeitam duas igrejas bem conhecidas: Nossa Senhora do Carmo no Recife e Nosso Senhor do Bonfim na Bahia. Os casos selecionados são reconhecidos por se associarem com o Xangô e o Candomblé. De acordo com uma breve contextualização de centros, tem-se uma análise de conteúdo das mensagens. Considerando as últimas, o destino e a natureza dos favores exigidos ou recebidos indicam uma mentalidade cultista íntima num meio católico externo. Em resumo, discutem-se duas interpretações. Uma examina o simbolismo dos grafitos em geral; a outra relata a manifestação do poder. ABSTRACT Writings on the wall: religious syncretism through graffiti in Northeast Brazil. v. 14, n. 2, p. 133-150, jan./jun. 1986. Syncretism between Catholicism and Afro-Brazilian cults is a well documented historical phenomenon. This preliminary study seeks to highlight the degree of contemporary religious interpenetration by examining the content of graffiti adorning the shrines of two well known churches: Nossa Senhora do Carmo in Recife and Nosso Senhor do Bonfim in Bahia. The selected cases are also acknowledged for their association with Xangó and Candomblé. According a brief contextualisation of the centres is provided before a content analysis of the messages is undertaken. Regarding the latter, both the terms of address and the nature of the favours requested or received indicate an inner cultist mentality in an outward Catholic environment. Two interpretations are briefly discussed. One examines the symbolism of graffiti in general; the other relates to the manifestation of power. RÉSUMÉ Inscriptions sur les murs: syncrétisme religieux á travers les graphitis dans le Nord Est du Brésil. v. 14, n. 2, p. 133-150, jan./jun. 1986. Le syncrétisme entre le catholicisme et les cultes afro-brésiliens est un phénomène historique bien documenté. Cette étude a pour but de mettre en relief l’interpénetration religieuse et contemporaine à travers l’analyse des graphitis qui ornent deux églises brésiliennes très connues: celle de Nossa Senhora do Carmo à Recife et Nosso Senhor do Bonfim à Bahia. Dans les deux exemples, on constate une association avec le “Xangô” et le “Candomblé”. On arrive à faire une analyse des contenus des messages à travers une breve contextualisation de différents centres. Cela est encore plus évident lorsqu’on observe le destin et la nature des faveurs exigées ou reçues, montrant qu’il y a une mentalité de culte intime par rapport au milieu catholique externe. En résumé, on étudie deux interprétations. La premiére liée au symbolisme des graphitis d’une manière générale, et la deuxième, à la manifestation du pouvoir.